2016
DOI: 10.1007/s12032-016-0801-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer treatment-related cardiac toxicity: prevention, assessment and management

Abstract: Cancer therapies, especially anthracyclines and monoclonal antibodies, have been linked with increased rates of cardiotoxicity. The development of some cardiac side effects happens over several months, and changes in ejection fraction can be detected long before permanent damage or disability occurs. Advanced heart failure could be averted with better and earlier detection. Methodologies for early detection of cardiac changes include stress echocardiograms, cardiac velocity measurements, radionuclide imaging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 63 publications
0
25
0
1
Order By: Relevance
“…The effectiveness of pixantrone in the current registry was also slightly better than in the aforementioned real-life retrospective study conducted in the UK, which reported median OS durations of 3.4 months, and an ORR of 24% (CR 10%; PR 14%), in a patient population similar to the current study. 11 In the UK registry, patients had received a median of 2 prior lines of chemotherapy, 99% had received rituximab, and 16% had undergone stem cell transplant, Ann Arbor stage was III-IV in 90% of patients and 73% had an IPI score of [3][4][5]11 while in our study, the median number of prior lines was 3, 96% had received rituximab, 16% had undergone transplant, 82.1% were Ann…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The effectiveness of pixantrone in the current registry was also slightly better than in the aforementioned real-life retrospective study conducted in the UK, which reported median OS durations of 3.4 months, and an ORR of 24% (CR 10%; PR 14%), in a patient population similar to the current study. 11 In the UK registry, patients had received a median of 2 prior lines of chemotherapy, 99% had received rituximab, and 16% had undergone stem cell transplant, Ann Arbor stage was III-IV in 90% of patients and 73% had an IPI score of [3][4][5]11 while in our study, the median number of prior lines was 3, 96% had received rituximab, 16% had undergone transplant, 82.1% were Ann…”
Section: Discussionmentioning
confidence: 46%
“…4 Anthracyclines are associated with cumulative cardiotoxicity, so their repeated use needs to be limited in patients with relapsed/ refractory NHL. 5,6 Therefore, for patients who require second-line therapy, platinum-based salvage regimens are recommended, with high-dose chemotherapy and autologous stem cell transplantation in eligible responding patients. 2 However, there is currently no recognised standard therapy for patients who fail first-and second-line therapies, or in those who are not eligible for stem cell transplantation.…”
mentioning
confidence: 99%
“…Currently, treatments for anthracycline-induced cardiotoxicity follow standard therapies for congestive heart failure [34]. Having more detailed information about the mechanisms that cause this toxicity could lead to targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…These sequelae can potentially transform cancer treatment into a chronic cardiovascular disease [3]. At present, cardiotoxicity has been associated with anthracyclines, monoclonal antibodies, tyrosine kinase inhibitors, proteasome inhibitors, anti-angiogenesis agents, and immunotherapy agents [4]. A classification system has been proposed to distinguish drugs that have the potential to induced irreversible cardiac damage (type I) versus drugs that predominantly induce reversible dysfunction (type II) [5].…”
Section: Introduction-scope Of the Problemmentioning
confidence: 99%